Godly clergy in early Stuart England : the Caroline Puritan movement, c. 1620-1643 - Webster, Tom (Cambridge studies in early modern British history., 1997)
This book reconsiders the existence of an early Stuart Puritan movement, and examines the ways in which Puritan clergymen encouraged greater sociability with their like-minded colleagues, both in theory and in practice, to such an extent that they came to define themselves as 'a peculiar people', a community distinct from their less faithful rivals. Their voluntary communal rituals encouraged a view of the world divided between 'us' and 'them'. This provides a context for a renewed examination of the thinking behind debates on ceremonial nonconformity and reactions to the Laudian changes of the 1630s. From this a new perspective is developed on arguments about emigration and church government, arguments that proved crucial to Parliamentarian unity during the English Civil War.